Profiling Covid-19 patients with respect to level of severity: an integrated statistical approach - Federica Cugnata; Maria Giovanna Scarale; Rebecca De Lorenzo; Marco Simonini; Lorena Citterio; Patrizia Rovere Querini; Antonella Castagna; Clelia Di Serio; Chiara Lanzani (Scientific Reports, 2023)
Abstract A full understanding of the characteristics of Covid-19 patients with a better chance of experiencing poor vital outcomes is critical for implementing accurate and precise treatments. In this paper, two different advanced data-driven statistical approaches along with standard statistical methods have been implemented to identify groups of patients most at-risk for death or severity of respiratory distress. First, the tree-based analysis allowed to identify profiles of patients with different risk of in-hospital death (by Survival Tree-ST analysis) and severity of respiratory distress (by Classification and Regression Tree-CART analysis), and to unravel the role on risk stratification of highly dependent covariates (i.e., demographic characteristics, admission values and comorbidities). The ST analysis identified as the most at-risk group for in-hospital death the patients with age > 65 years, creatinine $$\ge$$ ≥ 1.2 mg/dL, CRP $$\ge$$ ≥ 25 mg/L and anti-hypertensive treatment. Based on the CART analysis, the subgroups most at-risk of severity of respiratory distress were defined by patients with creatinine level $$\ge$$ ≥ 1.2 mg/dL. Furthermore, to investigate the multivariate dependence structure among the demographic characteristics, the admission values, the comorbidities and the severity of respiratory distress, the Bayesian Network analysis was applied. This analysis confirmed the influence of creatinine and CRP on the severity of respiratory distress.